Nauczyciel dla nauczycieli i wychowawców. Michał Friedländer jako popularyzator wiedzy o wychowaniu w latach międzywojennych - Michalska, Iwona (Studia Edukacyjne, 2018)
Michał Friedländer (1894-1942/1943?), a doctor of law by education, left his profession very quickly after his studies in Vienna. At the beginning, he conducted intensive educational project in Borysław and then, having moved to Krakow, became a teacher of German and induction to philosophy in the Private Co-Educational Gymnasium of the Jewish Society of Elementary and Secondary Schools [Żydowskie Towarzystwo Szkoły Ludowej i Średniej]. At the same time, he started cooperating with Polish and Jewish pedagogical and social magazines, where he published works dedicated mainly to the didactics of teaching modern languages and the education of children and teenagers. He was also the author of separate volumes and brochures dedicated to those issues. He sometimes also wrote about co-education, reading of children and teenagers, past and modern school reformers, and schools opened abroad as a result of new tendencies in education. He published information on functioning of out-of-school education in various European countries and held radio lectures, organized by the Ministry of Education, on the main assumptions of “new pedagogy”. Although he did not create new theories, his greatest services consisted in propagating thoughts and solutions resulting from various “new education” tendencies. He was probably one of few people in those years who consistently introduced teachers and educators to foreign reformist pedagogical ideas.